Effect of Fling-Step on Seismic Response of Steel Eccentrically Braced Frame Structures - B. Rezayibana; S. Norozikalehsar; B. Nourollahi (Numerical Methods in Civil Engineering)
Fling-step and forward directivity are two important characteristics of near-field earthquakes. Forward directivity occurs when the rupture propagates toward the site and arises in fault‐normal direction for strike‐slip faults. Fling-step is the consequence of permanent ground displacement imposed by near-field earthquakes and arises in strike-slip faults in the strike parallel direction. Fling-step effect produces permanent displacement at the end the culmination of displacement time history. This effect is usually omitted from the main record using the standard processing methods and therefore, cannot be determined for different structures. Many studies were performed to obtain seismic response of different structures subjected to near-field earthquake having forward directivity.  On the other hand, there are few references to investigate the effect of fling-step on seismic behavior of structures. For this purpose, 14 earthquake records with fling-step are selected in a way that important factors including fling-step, PGV, PGA and the energy application type are different. The selected records are applied to eccentrically braced frame structures with 3, 6, 9 and 12 stories. A nonlinear time history analysis is used to capture displacement and story-drift ratio responses. The results show that the fling-step effect has no significant impact on any of the considered structures and its effect can be neglected in the case of eccentrically braced frame structures.